Characteristics of immunity to leaf diseases of winter wheat samples under the conditions of the north-east forest steppe of Ukraine a - O. M. Osmachko; V. A. Vlasenko; O. M. Bakumenko; V. I. Bilokopytov (Regulatory Mechanisms in Biosystems, 2020)
To realize the genetic potential of the productivity of bread winter wheat varieties, it is necessary to maintain a certain level of plant resistance to disease. Resistance donors may lose this property as a result of changes in the virulence of the pathogen and defeat of the genetic systems of plant resistance. This makes it necessary to search for new resistance sources and donors to leaf diseases. Our researches were conducted using field, laboratory and mathematical-statistical methods. Phenological observations, accounting, evaluation and harvesting were conducted according to currently accepted methods. 86 bread winter wheat samples from the 4th WWSRRN CIMMYT were studied for resistance to leaf diseases in our research during 2014–2016. The manifestation of variability depended significantly on the genotype for three diseases. The highest genotype influence was obseved in resistance to septoria disease, where it was 81%. On average the highest indicator of resistance (7.7) to powdery mildew during the three years of research was observed in the mid-late ripening samples. The mid-early ripening group was considered to be the most adapted to the powdery mildew pathogen in the Northeastern Forest-Steppe. The highest average indicator of resistance (7.5) to brown rust for the three years of research was found in the early ripening group. The samples of the mid-ripening group were most adapted to the brown rust pathogen. The highest average resistance to septoria disease was also found in the early ripening group. The best adaptation to septoria disease was observed in mid-late ripening samples. 36% of the samples were resistant to three diseases. As a result of the research, a number of CIMMYT samples were isolated from the 4th WWSRRN, which exceeded the standard in resistance to powdery mildew, brown rust and septoria disease. They were characterized by better performance. Valuable forms for breeding work that can be resistance donors to leaf diseases were identified among them.